2014
DOI: 10.1037/a0035328
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing subjective responses to alcohol among adolescent problem drinkers.

Abstract: Theoretical models of alcoholism emphasize the acute reinforcing properties of alcohol as chief determinants of drinking, and animal research suggests adolescents are uniquely sensitive to these effects. Human studies of these phenomena, however, are virtually nonexistent. We used ecological momentary assessment methods to capture adolescents' subjective responses to alcohol in real time in their natural environments. Adolescent participants were 22 problem drinkers, ages 15 to 19 years (M = 18.3, SD = 0.09; 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 49 publications
4
58
0
Order By: Relevance
“…Potential explanations for these differences include the disparate assessment contexts and the examination of a higher BAC range in the present study. Notably, the use of in vivo assessments in the former study revealed high levels of stimulation before BAC levels were appreciable, possibly reflecting stimulation from the social context, and perhaps explaining the decline in stimulation as BAC increased (Miranda, et al, 2014). In contrast, the use of intravenous alcohol in this study served to remove non-pharmacological cues.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Potential explanations for these differences include the disparate assessment contexts and the examination of a higher BAC range in the present study. Notably, the use of in vivo assessments in the former study revealed high levels of stimulation before BAC levels were appreciable, possibly reflecting stimulation from the social context, and perhaps explaining the decline in stimulation as BAC increased (Miranda, et al, 2014). In contrast, the use of intravenous alcohol in this study served to remove non-pharmacological cues.…”
Section: Discussionmentioning
confidence: 87%
“…Examining links between subjective responses and craving can clarify in-the-moment processes by which subjective responses correspond with consumption (Miranda, et al, 2014; Rose, et al, 2010). Although other alcohol challenge studies have reported associations of alcohol-induced stimulation with craving (e.g., Bujarski & Ray, 2014; Ray, et al, 2010; Rose, et al, 2010), the present study addressed this question by modeling two discrete intervals of the BAC trajectory.…”
Section: Discussionmentioning
confidence: 99%
“…We expected that younger age would be associated with greater self-reported stimulation and lesser sedation among adolescents and young adults recruited in an ecologically valid setting and in the context of a natural drinking episode. Previous ecological momentary assessment (EMA) research found that adolescents experience greater stimulation while drinking in the natural environment, relative to adults, but this effect diminished at higher estimated eBACs (Miranda et al, 2014). Therefore, we also tested for interactive effects of age and eBAC, and expected that the relation of age to stimulatory responses to alcohol would be attenuated at higher eBACs.…”
Section: Introductionmentioning
confidence: 97%
“…These youth reached peak breath alcohol levels at a faster rate than is typical of adults administered a similar alcohol dose, while also showing smaller behavioral changes than anticipated given their BAC (Behar et al, 1983). A recent ecological study assessed dose-related changes in subjective ratings of stimulation and sedation on the ascending limb of intoxication using handheld wireless devices among a small sample of 29 adolescents aged 15 to 19 (Miranda et al, 2014). Youth were instructed to record subjective stimulatory and sedative states just before beginning to drink as well as their subjective responses following each of the first three standard drinks of a drinking episode, which produced an average estimated BAC (eBAC) equivalent to the Behar study (.04 mg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…These findings implicate craving as an important treatment target for pharmacotherapy. We also recently applied these methods to characterize adolescents’ subjective responses to alcohol use (87). Prior to this advance, because of legal and ethical restrictions on administering alcohol to underage youths in the laboratory, our understanding of how alcohol affects teenagers relied entirely on retrospective reports, animal models, and one small alcohol administration study with boys, ages 8 to 15, nearly 35 years ago (80).…”
Section: Introductionmentioning
confidence: 99%